2014
DOI: 10.1111/fare.12055
|View full text |Cite
|
Sign up to set email alerts
|

Daily Work Stress and Awakening Cortisol in Mothers of Individuals with Autism Spectrum Disorders or Fragile X Syndrome

Abstract: The effect of daily work stress on the next morning’s awakening cortisol level was determined in a sample of 124 mothers (M age = 49.89, SD= 6.33) of adolescents and adults with developmental disabilities and compared to 115 mothers (M age = 46.19, SD = 7.08) of individuals without disabilities. Mothers participated in 8 days of diary telephone interviews and provided saliva samples. Multilevel models revealed that mothers of individuals with developmental disabilities had lower awakening cortisol levels than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…A few studies have contrasted parenting stress in mothers who have a child with autism and mothers whose child has FXS [17,112]. These studies generally have found similar patterns for premutation carrier mothers of children with FXS and mothers of those with autism.…”
Section: Reviewmentioning
confidence: 99%
“…A few studies have contrasted parenting stress in mothers who have a child with autism and mothers whose child has FXS [17,112]. These studies generally have found similar patterns for premutation carrier mothers of children with FXS and mothers of those with autism.…”
Section: Reviewmentioning
confidence: 99%
“…Notably, we went further in this examination by piecing together findings from studies that showed that a higher stress was associated with higher bedtime cortisol levels (Zoccola & Dickerson, 2015) with studies that showed that some of these same variables are associated with higher waking cortisol the following day (Wong et al, 2014). These data support our previous statement that exploring day-to-day transaction between psychosocial and physiologic effects may provide a new avenue for assessing CAR, and perhaps the cortisol diurnal rhythm in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between bedtime cortisol on one day and CAR the following day is rarely explored. Studies also suggest that previous days’ stressors are associated with higher bedtime cortisol (Zoccola & Dickerson, 2015) and the next morning’s cortisol levels (Wong et al, 2014), and that these higher waking cortisol levels are associated with flatter CAR slopes (Adam et al, 2006). …”
Section: Expanding the Time Frame For Assessing Predictors Of The Cormentioning
confidence: 99%
See 1 more Smart Citation
“…Higher stress and negative emotions during a day are associated with lower morning cortisol awakening levels and lower CAR on the following day. There is, thus, a smaller difference between the morning cortisol level and the postawakening cortisol level (Proulx, Klee, & Oken, ; Wong et al, ). Having a sick child in need of medical care affects the parents’ mood (Angelhoff, Edéll‐Gustafsson, & Mörelius, ) and mothers have reported feeling less in control during accommodation at the paediatric ward (Angelhoff et al, ).…”
Section: Introductionmentioning
confidence: 99%